Peningkatan hasil belajar dan capaian tujuan pembelajaran mata kuliah ekonomi digital melalui penerapan model pembelajaran CORE - Mardiana Firdaus, Riril; Alim Ba'diya Kusufa, Roni Alim Ba'adiya; Mariani Manik, Yuni (Jurnal Riset Pendidikan Ekonomi, 2024)
The aim of this research is to develop a design for the CORE (Connecting, Organizing, Reflecting, Extending) learning model which is implemented in the Digital Economy course. This course is designed to develop students' understanding of the digital economy, covering topics such as disruption, industrial revolution, and various aspects of digital transformation in Indonesia, including E-Commerce, electronic commerce business models, digital infrastructure, the latest technologies such as the Internet, big data, currency digital, and e-Environment implementation. This research is a type of research and development which aims to create certain products and evaluate their effectiveness. This research adopts the development model of ADDIE instructional design which includes the stages of analysis, design, development, implementation and evaluation. The research results show that the CORE learning model is successful in improving student learning outcomes. Apart from that, the results of this research also show that the specified learning outcomes have been achieved thanks to increased student learning outcomes. There has been a change in learning outcomes which can be seen from changes in student behavior in following the learning process in accordance with the predetermined design.